2002
DOI: 10.1089/10430340252769725
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graft-Versus-Host Disease-Inducing Capacity of T Cells After Activation, Culturing, and Magnetic Cell Sorting Selection in an Allogeneic Bone Marrow Transplantation Model in Rats

Abstract: Graft-versus-host disease (GvHD), a major complication of allogeneic bone marrow transplantation, has been ascribed to mature T cells in the graft. Because T cells play an important role in engraftment of the bone marrow and decrease the probability of relapse of leukemia, a treatment strategy was developed to preserve the benefits of T cells in the graft and to control the severe complications of GvHD. This can be accomplished by the genetic modification of donor T cells with a suicide gene that allows their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Data from both mouse and human allogeneic studies have shown that donor T cells exhibit decreased allo-reactivity and GVHD potential following ex vivo activation and expansion [2][3][4][5][6]. This loss of allo-reactivity is extremely undesirable because both the conversion to full donor chimerism and the anti-leukemia effect after allogeneic HSCT are mediated, at least in part, by alloreactive donor T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from both mouse and human allogeneic studies have shown that donor T cells exhibit decreased allo-reactivity and GVHD potential following ex vivo activation and expansion [2][3][4][5][6]. This loss of allo-reactivity is extremely undesirable because both the conversion to full donor chimerism and the anti-leukemia effect after allogeneic HSCT are mediated, at least in part, by alloreactive donor T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the therapeutic strategies that are being developed to control GVHD while maintaining the beneficial graft-versus-leukemia and/or graft-versus-infection effects provided by donor lymphocyte infusion after allogeneic HSCT require ex vivo T cell stimulation and expansion. Unfortunately, multiple preclinical and clinical studies have demonstrated that these ex vivo expanded T cells exhibit decreased survival and function in vivo, including reduced alloreactivity and GVHD potential [2][3][4][5][6]. Recently, others and we described an ex vivo method for expansion of human T (huT) cells, using anti-CD3 and anti-CD28 monoclonal antibodies that are covalently attached to superparamagnetic microbeads (CD3/CD28 beads) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…18 In short, donor BM cells were obtained by flushing the cavity of WR rat tibias and femurs with RPMI 1640 (Invitrogen, Carlsbad, CA). A single-cell suspension was obtained by filtering the BM through a cell strainer (100-m filter, Falcon; Becton Dickinson Labware, Franklin Lakes, NJ).…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%
“…In addition, we observed that the IL-2 proliferation response was significantly higher in samples that had been subjected to transduction under standard stimulatory conditions (1 mg/ml anti-CD3i/ anti-CD28i) compared to those activated with 1 mg/ml anti-CD3i (Figure 1a). Since previous studies showed that cell selection could alter the functionality -including the GVHD reactivity -of transduced cells, 17,19,28 we have investigated whether or not the immunomagnetic cell sorting of cells expressing the selectable tNGFR transgene modifies the proliferative response of T cells to IL-2. The experiments in Figure 1b show that no differences in the proliferative response of T cells to IL-2 were observed between transduced unselected cells with respect to the NGFR þ (96% NGFR þ ) and NGFR À (o10% NGFR þ ) fractions collected after immunoselection.…”
Section: Resultsmentioning
confidence: 99%